Scaling up structured lifestyle interventions to improve the management of cardiometabolic diseases in low-income and middle-income countries: a systematic review of strategies, methods and outcomes - Kavumpurathu R Thankappan; Biraj Karmacharya; Jeemon Panniyammakal; Brian Oldenburg; Abha Shrestha; Lu Yang; Getu Debalkie Demissie; Rolina Dhital; Tilahun Haregu; Ganeshkumar Parasuraman; Sabrina Gupta (BMJ Public Health)
Introduction Cardiometabolic diseases (CMDs), the leading causes of death in low-income and middle-income countries (LMICs), are proven to be mitigated through structured lifestyle interventions (SLIs—dietary changes, physical activity, tobacco cessation and alcohol intake), but the challenge lies in scaling them up in LMICs. Therefore, we undertook a systematic review to identify the strategies, methods and outcomes used in scaling up SLI programmes to improve cardiometabolic outcomes in LMICs.Methods We searched studies implementing scale-up strategies (delivery approaches enhancing an intervention’s adoption, implementation and sustainability), methods (theories, models and frameworks) and present outcomes (feasibility, fidelity, etc) following the Proctor E framework. We searched six databases to identify studies published in English with no time restriction, guided by the Setting, Perspective, Intervention, Comparison and Evaluation framework. Quality assessment was performed using the Cochrane risk-of-bias, National Institutes of Health and Joanna Briggs Institute tools. Given the heterogeneity of the outcome measures, we conducted a narrative synthesis of the extracted information.Results Out of the 26 studies included, 18 (69%) adapted SLI interventions to suit local contexts. Strategies such as system integration, strengthening facility services and training led to up to 100% attendance of participants. Notably, only four studies (15%) used theories, models and frameworks for the full scale-up process, which is crucial for large-scale implementation in resource-limited settings. 15 (58%) studies reported the feasibility of scale-up, whereas 7 (27%) reported no significant differences in lifestyle behaviours or CMD biomarkers.Conclusions Early community and local stakeholders’ engagement is crucial for codeveloping strategies for the scale-up of SLIs. Conducting readiness assessments and system integration are all essential considerations for improving scale-up outcomes. Additionally, we strongly recommend using suitable frameworks to guide the scale-up of SLIs to maximise the benefit for the population.